Comparison of Micro-Computed Tomography and Digital Intraoral Radiography to Determine the Accuracy of Digital Radiographic Measurements of Mandibular Molar Teeth in Dogs. (December 2017) - Marron, Louise; Rawlinson, Jennifer; McGilvray, Kirk; Prytherch, Ben
Introduction: The purpose of this study was to compare root and root canal width measurements between digital intraoral radiography (IOR) and micro-computed tomography (μCT). The accuracy of IOR measurements of canine mandibular molars was scrutinized to assess feasibility of developing a model to estimate animal age based on dentinal thickness. Materials and Methods: Thirty-nine canine mandibular first molars were imaged using μCT and IOR. For each tooth, the root and root canal width of the mesial and distal roots were measured by a single observer at 3 marked sites on μCT and IOR. Two different software programs were used to measure the radiographs. The radiograph measurements were compared to each other and to the μCT measurements. The μCT images were considered the anatomic reference standard for structural representation. Results: The data collected demonstrated IOR bias and variability throughout all measurement sites, with some sites being more affected than others. Neither IOR system produced unbiased measurements that closely reflected the μCT measurements consistently. The overall lack of agreement between measurements demonstrated the difficulties in developing a standardized protocol for measuring root and root canal width for the first molar teeth in dogs. Conclusion: Developing a protocol to accurately measure and compare μCT and IOR measurements is challenging. Designing a measurement system that would allow for universal application to age dogs would require continued research utilizing a standardized approach to overcome the limitations identified in this article.